2015
DOI: 10.1155/2015/292076
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Nicotine Application Attenuates Cardiac Dysfunction after Severe Thermal Injury

Abstract: Background. Severe burn trauma leads to an immediate and strong inflammatory response inciting cardiac dysfunction that is associated with high morbidity and mortality. The aim of this study was to determine whether transdermal application of nicotine could influence the burn-induced cardiac dysfunction via its known immunomodulatory effects. Material and Methods. A standardized rat burn model was used in 35 male Sprague Dawley rats. The experimental animals were divided into a control group, a burn trauma gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(62 reference statements)
0
7
0
Order By: Relevance
“… 19 In their study, Van Maanen et al 20 showed that intraperitoneally nicotine application to mice could alleviate clinical rheumatoid arthritis. In addition, Leib et al 21 showed that nicotine reduces inflammation in a mouse model of autoimmune Myocarditis and Claassen et al 35 , 36 verified an antiinflammatory effect of Nicotine after burn trauma. In clinical studies, the anti-inflammatory effect of nicotine has been verified in patients suffering from ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“… 19 In their study, Van Maanen et al 20 showed that intraperitoneally nicotine application to mice could alleviate clinical rheumatoid arthritis. In addition, Leib et al 21 showed that nicotine reduces inflammation in a mouse model of autoimmune Myocarditis and Claassen et al 35 , 36 verified an antiinflammatory effect of Nicotine after burn trauma. In clinical studies, the anti-inflammatory effect of nicotine has been verified in patients suffering from ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of VNS were mediated by nicotinic receptors since they were blocked by hexamethonium but unaffected by atropine. Consistent with nicotinic receptor mediation of responses to VNS, transdermal administration of nicotine to rats at the time of burn injury attenuated or inhibited elevation of tissue pro-inflammatory cytokine levels, normalized blood pressure, and improved myocardial contractile function (Claassen et al, 2014; Claassen et al, 2015). While these were primarily acute studies, other investigators have demonstrated that treatment with GTS-21 increases 7-day survival in burned mice to 100% as compared to 25% in saline treated mice (Khan et al., 2012).…”
Section: Impact Of Cholinergic Therapy and α7nachrs In Models Of Smentioning
confidence: 97%
“…Transdermal nicotine has already been found to be highly effective in attenuating life-threatening cardiac dysfunction triggered by severe burns. 8 Therapeutic benefits were associated with anti-inflammatory and immunomodulating effects of nicotine in this study. 8 Nicotine has been demonstrated to interact with a target—the α7 nicotinic acetylcholine receptor (α7nAChR)—for attenuation of proinflammatory cytokine release.…”
mentioning
confidence: 63%